PHILOSOPHER-ENCYCLOPEDIST ABU RAYKHAN BERUNIY (ResearchJet Journal of Analysis and Inventions, 2024)
The article shows that the first half of the 11th century and the two centuries preceding it were characterized by the rapid development of the culture of the peoples of the Middle East and Central Asia. The works of Central Asian astronomers and mathematicians of this period are widely known. Among them, a place of honor is occupied by Abu Raykhan Beruniy, who is to this day a scientist all over the world.